1981
DOI: 10.1021/jo00339a034
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and ring-opening reactions of functionalized sultines. New approach to sparsomycin

Abstract: An efficient route leading to the functionalized five-membered cyclic sulfinate esters (y-sultines) 14a,b and 21a,b is described on the basis of the reaction of the N-protected cystinol derivatives 11 and 20, respectively, with N-chlorosuccinimide (NCS) and AcOH. Ring-opening reactions of the sultines can be performed in two ways. Treatment of 14 with Clz or NCS/HCl gives the sulfonyl chloride 15 by cleavage of the C-O bond. Selective cleavage of the S-OR bond occurs when 14 or 21 is treated with MeSCH2Li, n-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 3 publications
(9 reference statements)
0
21
0
Order By: Relevance
“…Synthesis: The syntheses of compounds 1-14 either were performed as reported [45][46][47] or are described in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis: The syntheses of compounds 1-14 either were performed as reported [45][46][47] or are described in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleophilic attack on the cysteine-derived chiral 4-amino-1,2-oxathiolane 2-oxide 298 by alkyllithiums takes place on the sulfur atom with inversion of configuration to give 299 (Scheme 11.98) [245].…”
Section: Nucleophilic Attackmentioning
confidence: 99%
“…Figure 11.2 Geometry of a 1,2-oxathiolone derivative. Oxathiolane 277 is prepared by treatment of N-alkylcystinol 276 with NCS or NBS (Scheme 11.87) [233]. Substituted 1,3-thioalcohols 278 can also be oxidized with NaIO 4 to give the corresponding 1,2-oxathiolane-2-oxides 279 (Scheme 11.88) [234].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] These potentially important biological activities have made 3 an attractive target for a potential antineoplastic compound. 11) Since thê rst synthetic study of sparsomycin in 1976, 12) synthetic studies of sparsomycin, [13][14][15] total synthesis, [16][17][18] biosynthesis, 19,20) and structure-activity relationship studies [21][22][23][24][25][26][27] have been widely reported. There have been many reports on the antitumor, antibacterial, antifungal, and antiviral properties; however, normalization of the phenotype of oncogene-transformed cells by 3 and its analogues has not previously been reported.…”
mentioning
confidence: 99%